Role of insurance in the development of India’s micro, small and medium enterprise (MSMEs) / Abhijit Chakraborty and Ashim Kr Das - Chakraborty, Abhijit; Kr Das, Ashim (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
This paper investigates the role of Insurance in the development of Micro, Small and Medium Enterprises (MSMEs) in India. MSMEs have been accepted as a crucial component of an economy irrespective of the phase of development it is in. It is estimated that more than 95% of the enterprises across the world are MSMEs, employing around 60% people in the private sector. The MSMEs are considered key elements in the development of every nation. In India, MSME sector contributed 28.77% in GDP in 2016-17 with 63 million enterprises and employment of 110 million people. Despite its size, MSMEs cumulatively act as foundation of a stable economy and plays a significant role in the sustainable economic growth of a nation. However, the inherent features of MSMEs including limited financial and managerial capability cause them to face financial and strategic risks. Sustainability of the MSMEs can be supported by eliminating the credit gap and ensuring enhanced access to finance. The provision of financial support by financial intermediaries like banks can be augmented with proper risk management by the MSMEs with the help of Insurance Sector. The study concludes that insurance can play a significant role in the development of MSMEs by providing them adequate risk protection and thus enhancing their access to finance